Methodological quality of football studies based on observational methodology: A sistematic review - López-Arenas, Daniel; Sanduvete-Chaves, Susana; Anguera, M. Teresa; Chacón-Moscoso, Salvador (Anales de Psicología / Annals of Psychology, 2026)
Observational methodology (OM) has been extensively employed in football research. This study presents a systematic review that applies the Methodological Quality Scale for studies based on Observational Methodology (MQSOM) to 236 primary papers on football based on OM to unveil methodological trends. The psychometric properties of the MQSOM yielded adequate results. Descriptive statistics were provided; a proportion analysis was conducted to identify differences in procedures; and a two-step cluster analysis was conducted to identify methodological quality (MQ) profiles. The proportion analysis revealed significant differences in observation type (frequently direct), coding manual (often specified), data type (seldom specified), observational instrument (frequently specified), recording (often specified), control (occasionally specified) and analysis software (frequently specified), parameter type (usually frequency), quality control (frequently employed), and analysis (usually non-descriptive). Two-step cluster analysis yielded five MQ profiles ranked in decreasing order based on the MQSOM score (P1: high Design Quality -DQ-, and Measurement & Analysis Quality -MAQ-; P2: moderate DQ, high MAQ; P3: low DQ, high MAQ; P4: low DQ, moderate MAQ; and P5: low DQ and MAQ). This work presents an updated snapshot of OM applied in football research, outlining future improvements in MQ.